An ICET- A survey on Hypoparathyroidism in Patients with Thalassaemia Major and Intermedia: A preliminary report - De Sanctis, Vincenzo; Soliman, Ashraf T.; Canatan, Duran; Elsedfy, Heba; Karimi, Mehran; Daar, Shahina; Rimawi, Hala; Christou, Soteroula; Skordis, Nicos; Tzoulis, Ploutarchos; Sobti, Praveen; Kakkar, Shruti; et al. (Acta Biomedica Atenei Parmensis, 2018)
Hypoparathyroidism (HPT) is a rare disease with leading symptoms of hypocalcemia, associated with high serum phosphorus levels and absent or inappropriately low levels of parathyroid hormone (PTH). In patients with thalassemias it is mainly attributed to transfusional iron overload, and suboptimal iron chelation therapy. The main objectives of this survey were to provide data on the prevalence, demographic and clinical features of HPT in thalassemia major (TM) and intermedia (TI) patients living in different countries, and to assess its impact in clinical medical practice. A questionnaire was sent to all Thalassemia Centres participating to the International Network of Clinicians for Endocrinopathies in Thalassemia and Adolescence Medicine (ICET-A) Network.Seventeen centers, treating a total of 3023 TM and 739 TI patients, participated to the study. HPT was reported in 206 (6.8%) TM patients and 33 (4.4%) TI patients. In general, ages ranged from 10.5 to 57 years for the TM group and from 20 to 54 years for the TI group. Of the 206 TM patients and 33 TI patients with HPT, 117 (48.9%) had a serum ferritin level >2.500 ng/ml (54.3% TM and 15.1% TI patients) at the last observation. Hypocalcemia varied in its clinical presentation from an asymptomatic biochemical abnormality to a life-threatening condition, requiring hospitalization. Calcium and vitamin D metabolites are currently the cornerstone of therapy in HPT. In TM patients, HPT was preceded or followed by other endocrine and non-endocrine complications. Growth retardation and hypogonadism were the most common complications (53.3% and 67.4%, respectively). Although endocrine complications were more common in patients with TM, non-transfused or infrequently transfused patients with TI suffered a similar spectrum of complications but at a lower rate than their regularly transfused counterparts.In conclusion, although a large international registry would help to better define the prevalence, comorbidities and best treatment of HPT, through the result of this survey we hope to give a clearer understanding of the burden of this disease and its unmet needs. HPT requires lifelong therapy with vitamin D or metabolites and is often associated with complications and comorbidities.Therefore, it is important for endocrinologists and other physicians, who care for these patients, to be aware of recent advances of this disorder.